Strategi Guru PPKn dalam Mengembangkan Sikap Toleransi Peserta Didik Kelas X E-7 Menggunakan Pendekatan Active Learning Tipe True or False di SMA Negeri 2 Sipora Kepulauan Mentawai - Siahaan, Falentina; Juliardi, Budi; Jamurin, Jamurin (Darul Yasin Al Sys, 2023)
This research is motivated by the attitude problems of students in class X E-7 which are considered quite good, but the implementation has not been optimal, especially the character of tolerance in learning Civics at SMA Negeri 2 Sipora. The purpose of this research is to introduce the strategy active learning type true or false on students class X E-7 at SMA Negeri 2 Sipora. This study aims to describe the implementation and constraints in the strategy active learning type true or false., as well as describing solutions in overcoming obstacles to implementing the strategy active learning type true or false in increasing the tolerance attitude of class X E-7 students through Civics subjects at SMA Negeri 2 Sipora, Mentawai Islands Regency. The type of research used is qualitative research with descriptive methods, the research informants are school principals, Civic Education teachers, and students. Data collection techniques used, namely observation techniques, interviews, and documentation studies. Data processing with data analysis with data reduction steps,display data, and drawing conclusions/verification. The results of the research show that the implementation of the strategy active learning type true or false in PPKn subjects in class X E-7 it is considered quite fun and does not make students bored and is very suitable for use by PPKn teachers in the last lesson. Excellence, strategi active learning type true or false This can form teamwork, train students to think critically, be active, and can also instill an attitude of tolerance in students in class X E-7 SMA Negeri 2 Sipora. Meanwhile, constraints in the implementation of the strategy active learning type true or false is that PPKn teachers must have mature preparation physically, materially, and knowledge. Meanwhile, the obstacle in terms of tolerance is the unification of the perceptions of each individual. Civics teacher's solution in overcoming obstacles in implementing strategies true or false, namely (1) prepare yourself physically, materially, and emotionally and accompanied by knowledge, (2) must carry out teaching exercises using strategies true or false gradually, (3) look for creative learning strategies to make students active and not get bored quickly while learning in class, and (4) evaluate learning strategy activities true or false which has been implemented. SMA Negeri 2 Sipora has a Youth Character Development Program and a Religious Literacy Program to instill values of tolerance and deepen their respective religious knowledge.